2015
DOI: 10.1161/circresaha.115.306233
|View full text |Cite|
|
Sign up to set email alerts
|

TRAF6-Mediated SM22α K21 Ubiquitination Promotes G6PD Activation and NADPH Production, Contributing to GSH Homeostasis and VSMC Survival In Vitro and In Vivo

Abstract: Recently, glucose metabolism has been highlighted as part of a novel mechanism involved in the complex regulation Molecular Medicine© 2015 American Heart Association, Inc. Objective: To identify the relationship between dihydronicotinamide adenine dinucleotide phosphate production and SM22α activity in the development and progression of vascular diseases. Methods and Results:We showed that the expression and activity of glucose-6-phosphate dehydrogenase (G6PD)are promoted in platelet-derived growth factor (PDG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 40 publications
3
40
0
Order By: Relevance
“…Upon exposure to irradiation, ATM kinase promotes G6PD activity to enhance nucleotide production33. Post-translationally, G6PD is modified by lysine acetylation, phosphorylation, ubiquitination and O-GlcNAcylation34353637. We previously found that G6PD is deacetylated and activated by SIRT238, which led us to explore the possibility of targeting SIRT2 to suppress G6PD and leukaemia394041.…”
Section: Discussionmentioning
confidence: 99%
“…Upon exposure to irradiation, ATM kinase promotes G6PD activity to enhance nucleotide production33. Post-translationally, G6PD is modified by lysine acetylation, phosphorylation, ubiquitination and O-GlcNAcylation34353637. We previously found that G6PD is deacetylated and activated by SIRT238, which led us to explore the possibility of targeting SIRT2 to suppress G6PD and leukaemia394041.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of intimal SMCs within atherosclerotic lesions are derived from resident medial SMCs that undergo phenotypic modulation and migration into the intima, where they proliferate (18,34). PDGF-BB-treated VSMCs display increased activity of migration and proliferation, accompanied with decreased SM22␣ expression (8,18,21,35), leading to the speculation of a negative correlation between VSMC migration and SM22␣ expression. The present study provided evidence that overexpression of SM22␣ inhib-C765 SM22␣ IN VSMC LAMELLIPODIUM FORMATION its PDGF-BB-induced cell migration in synthetic VSMCs and that disruption of SM22␣ promotes migratory responses after artery ligation.…”
Section: Discussionmentioning
confidence: 99%
“…NADPH works as cellular reducing agent and it plays a critical function in maintaining redox balance and biosynthesis of macromolecules. NADPH is generated by metabolic enzymes such as 6‐phosphogluconate dehydrogenase (6PGD) , glucose‐6‐phosphate dehydrogenase (G6PD) of the pentose phosphate pathway (PPP) , isocitrate dehydrogenases (IDHs) , and malic enzymes (MEs). These enzymes which are associated with the production of NADPH are currently reported as potential therapeutic targets for cancer .…”
Section: Introductionmentioning
confidence: 99%